Efeito de polimorfismos no receptor do hormônio do crescimento (GHR) e no fator de crescimento semelhante à insulina tipo 1 (IGF-I) no intervalo parto-concepção e produção de leite de vacas da raça Holandês - Hax, Lucas Teixeira (2013)
The genes of the somatotropic axis, which act regulating the metabolism and physiology of the mammals, present polymorphism associated to some characteristics of economical interest, such as reproductive performance and milk production. Such factors may be influenced by the mutation on only one nucleotide in the base sequence of the gene of the growth hormone receptor (GHR), which may alter the density of GHR on the hepatic tissue. Changes in the coupling of the growth hormone (GH) in the hepatic tissue alter the serum concentration of the insulin-like growth factor 1 (IGF-I), as IGF-I is produced mainly by the liver when it is stimulated by the growth hormone. Different studies have evaluated the effect of polymorphisms in the gene responsible for encoding IGF-I on the reproductive performance and milk production of high production dairy cows. Among other functions, the IGF-I mediates the effects of gonadotropins on the follicular cells, stimulating the growth and differentiation of theca and granulosa follicular cells, playing also a significant role on the final growth and maturation of the dominant follicle. Furthermore, high serum IGF-I concentrations are associated with a earlier return to cyclicity post partum in high yield dairy cows. Thus, the objective of this study was to evaluated the relevance of the mutations in GHR and IGF-I on the calving conception interval, number of inseminations per pregnancy and milk production in Holstein cows. One hundred and fifty five Holstein cows, submitted to a semi extensive management system, subjected to fixed-time artificial insemination (TAI) that got pregnant up to 250 days in milk in 2011, were selected. Among the animals tested, 29% presented GHR AluI (+ / +), 57.5% AluI (+ / -) and 13.5% AluI (- / -) genotype. 34.9% presented IGF-I SnaBI (+ / +), 45.8% SnaBI (+ / -) and 19.3% SnaBI (- / -) genotype. No association was observed between GHR AluI and IGF-I SnaBI genotypes and calving conception interval, number of inseminations per pregnancy and milk yield (P> 0.05). Likewise, there was no association between the interaction of GHR AluI and IGF-I SnaBI genotypes and calving conception interval, number of inseminations per pregnancy and milk yield (P> 0.05). Finally, further studies are necessary to better understand the relevance of GHR AluI and IGF-I SnaBI genotypes to the calving conception interval number of inseminations per pregnancy and milk production in Holstein cows.